INTERACTION BETWEEN YAZYCHNYTSTVO AND CHRISTIANITY IN KYIVAN RUS: REFLECTIONS ON THE JAPANESE EXPERIENCE OF FORMING A COMBINED RELIGIOUS TRADITION. - O. M., Mostipan; O. M., Мостіпан (Hileya: Scientific Bulletin / Gileya, 2023)
The theoretical basis of this study is the concept of «parallel development». A good example of the application of this concept in socio-political studies is Hajime Nakamura’s book «A Comparative History of Ideas». The general idea is that in the course of historical development, different peoples and cultural regions have had similar ideas, concepts, problems or tasks that needed to be solved. In this regard, a certain intellectual discourse was formed, which became the property of world cultural development and is the subject of research in the history of intellectual thought. Using this concept of «parallel development», it is possible to make a projection on the parallel processes that took place in cultural development in different regions and countries of the world, in particular, to study the impact of these processes on the future fate of countries and the results of the impact of public policy on these processes. In this study, the processes of penetration of world religions, namely Buddhism in Japan and Christianity in Kyivan Rus, which took place in a relatively similar time period, are considered as «parallel processes». In this regard, attention is drawn to the specifics of the state policy of Kyivan Rus regarding religious processes, their respective impact on the sphere of culture, politics and further development of the state. The article also draws parallels with the Japanese experience of attracting a new religion – Buddhism, and compares the practical results of the impact of new religions on social processes in the states. In this study, the transliteration of the term «yazychnytstvo» from Ukrainian into English will be used, although in some sources the term «yazychnytstvo» is translated into English as «paganism».